Relasi Kuasa Michel Foucault dalam Perspektif Musik dan Pertunjukan: Subversi Kebudayaan Komunitas Lima Gunung Magelang - Bahtiar Arbi (Musikolastika: Jurnal Pertunjukan dan Pendidikan Musik, 2022)
The Komunitas Lima Gunung is a forum for traditional artists who live in mountainous areas around Magelang, namely Merapi, Merbabu, Andong, Menoreh, and Sumbing. This community was initiated by Sutanto Mendut as a medium of communication between traditional artists and an effort to keep traditional arts alive, both related to ritual arts which have certain packages in their performances and profane art that is free of creation. This research uses a cultural approach paradigm. Case study and ethnographic research design in the Komunitas Lima Gunung. Primary data sources were obtained from the artists of the Komunitas Lima Gunung, and secondary data sources were obtained from exhibition catalogs, media publications, and cultural observers. Data collection techniques were carried out through participant observation, in-depth interviews, and document studies. Data analysis was carried out interactively back and forth from various phases, namely data collection, data reduction, data presentation, and drawing conclusions. The result of this research is that the cultural subversion promoted by Sutanto Mendut and the Komunitas Lima Gunung requires an alternative culture or a counter culture culture. Cultural subversion initiated by Sutanto Mendut and the Komunitas Lima Gunung rejects the domination and hegemony of certain cultures over other cultures. Instead, it gave rise to many versions of culture from various communities. The various versions of culture are not only an identity, but also a source of inspiration for various creations, both discourses, expressions, and cultural products. Culture is also able to support the life force of its people in the midst of the state's neglect of its people. People become more independent of the state so that they have a high bargaining position. Ideally, through culture, the people can be reached back to their ownership.